PENGARUH PLUMBUM (Pb) TERHADAP STRUKTUR INSANG IKAN MAS (Cyprinus carpio, L) - Natalia, Mariani (Jurnal Perikanan dan Kelautan, 2007)
A study on the hystopathology of the gill of Carp (Cyprinus carpio) has beenconducted from January – March 2005 in the laboratory of Parasites and FishDiseases of the Fishery and Nlarine Sciences of Riau University, Pekanharu. Thisstudy aims to understand the effects of Plumbum (Pb) polluted water towardshistological structure of the gills. Results of this study indicated that the presenceof Pb in the water significantly affects the gill structure. The cartilage becamelengthened and damage, primary and secondary lamellae swollen, haemorrhageand necrosis are present.